2004
DOI: 10.1021/jp046913n
|View full text |Cite
|
Sign up to set email alerts
|

Charge Loss in Gas-Phase Multiply Negatively Charged Oligonucleotides

Abstract: In an attempt to shed light on the mechanism by which gaseous samples of negatively charged oligonucleotides undergo extremely slow (i.e., over 1-1000 s) charge loss, we have carried out molecular dynamics simulations on an oligonucleotide anion, T 5 3-, containing five thymine, deoxyribose, and phosphate units in which the first, third, and fifth phosphates are negatively charged. The study is aimed at determining the rate at which an electron is detached from such a trianion by way of an internal Coulomb rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The "terminal effect" has so far not been reported in literature, but the distinct conditions upon which such dissociation pathway is observed suggest that electronic and steric factors are involved. A possible explanation is based on a study of Anusiewicz et al, who performed molecular dynamics simulations on a DNA 5-mer (T 5 3-) with zero and three negative charges on the backbone to investigate the effect of increased Coulombic repulsion on the gas-phase structure [40]. It was shown that a 3-fold negatively charged pentamer is likely to adopt an elongated, stretched configuration, whereas the same ON with a neutral backbone is arranged in a rather compact structure.…”
Section: Gas-phase Fragmentation Of Highly Charged Oligodeoxynucleotidesmentioning
confidence: 99%
“…The "terminal effect" has so far not been reported in literature, but the distinct conditions upon which such dissociation pathway is observed suggest that electronic and steric factors are involved. A possible explanation is based on a study of Anusiewicz et al, who performed molecular dynamics simulations on a DNA 5-mer (T 5 3-) with zero and three negative charges on the backbone to investigate the effect of increased Coulombic repulsion on the gas-phase structure [40]. It was shown that a 3-fold negatively charged pentamer is likely to adopt an elongated, stretched configuration, whereas the same ON with a neutral backbone is arranged in a rather compact structure.…”
Section: Gas-phase Fragmentation Of Highly Charged Oligodeoxynucleotidesmentioning
confidence: 99%
“…Thermal electron detachment time constants were in the order of 1-1000 s for dB7 (3- 2-) for various base sequences between 100 and 150 °C. Anusiewicz and co-authors 75 proposed that this electron autodetachment from the ground state could be due to geometrical fluctuations of the oligonucleotide causing fluctuations in the Coulomb potential at a phosphate site of sufficient magnitude (estimated as 5 eV, which is the electron binding energy of H2PO4 -) so that the electron can tunnel through the Coulomb barrier, the rate-limiting step being the rate at which geometrical fluctuations bring the oligonucleotide in a favorable conformation for electron autodetachment. The computed electron autodetachment rate of dT5 3was 0.02-0.5 s -1 at T = 170 °C.…”
Section: Comparison Between Electron Photodetachment Thermal Autodetmentioning
confidence: 99%
“…Proteins and DNAs can be easily transferred to the gas phase with a high charge state by electrospray , and can be used as prototypes to study detachment mechanisms in highly charged anions and also the influence of the molecular flexibility on detachment. , Gas phase MCAs of DNA have driven many interests , in relation with their redox properties and with photoinduced damages in solution. Recently, we performed energy-resolved spectroscopy experiments on gas phase MCAs of DNAs. , We observed electron detachment and showed that this detachment was strongly base dependent.…”
Section: Introductionmentioning
confidence: 99%